Deep learning for fusing speech and text for detection of Alzheimer’s Disease - Tan, Jun Xian (Nanyang Technological University, 2022)
Alzheimer’s Disease (AD) is one of the most common forms of dementia which occurs mainly in elderlies. Extensive research has been done to find a cure. However, early intervention is just as important. Impaired speech, which occurs in the early stages of AD, could be used as a biomarker for early detection of AD. Impaired speech could provide useful information, such as audio and text features, to be used for detection of AD.